Recrutá-los jovens: a formação de aprendizes marinheiros em Sergipe e Lisboa (1868-1905) - Solyane Silveira Lima (2013)
This thesis presents as an object of historical research the formation of children and youth in sailor activities developed in Seamen Apprentices Company of Sergipe and Seaman Students School of Lisbon. The purpose is to discuss that such education was aimed not only the professional training for the supply of the lack of skilled labor for the naval services, but also for the moral education of underprivileged children and young people as a topic for social inclusion. In addition to this issue, the rise of social control by the State was observed in the nineteenth century to the detriment of charitable and philanthropic practice accomplished by other society institutions, noting the emergence of public welfare and the role of the State in the formation of poor children for military staff. The temporal boundaries refer to the establishment date of the Seamen Apprentices Company of Sergipe in 1868 and the transition time and a new organization reopening of this institution in 1905, the Seamen Apprentices School of Sergipe. This timeframe also includes the creation and extinction of Seaman Students School of Lisbon, which operated from 1876 to 1895. To situate historically the theme, a study was conducted about the process of the naval workforce training and the military instruction as an alternative education to underprivileged children. For discussion of the conceptual development of the research field that associated the childhood protection with moralizing, studies on the history of social education developed by Julio Ruiz Berrio were taken as reference. According to this author, as humanity has progressed there was also an increase in the number of marginalized people, including children, and as social structures became more complex, the need for social education has increased, that is, an education type for the marginalized and excluded people with essential purpose of recovery and social inclusion through work. Thus, it is intended to investigate the pedagogical proposal developed in the Seaman Apprentices Company, discussing the differences of training for children and youth destitute with regular public school education, in expansion at the time. Regarding Seamen Students School of Lisbon the proposal is to investigate the similarities with the institution of Sergipe, since both were intended to empower life through learning a craft. For this study, the following Brazilian documentary sources were selected : national and local legislation, reports of government (presidential and State messages ), public instruction regulations of Sergipe, newspapers, correspondences, and various crafts. And in Portugal was examined: laws, institution regulations, crafts, maps, inspection records and students certificates.